Self-Leadership and Nurses Competence in Infection Prevention and Control in Hospital: Self-Leadership and Nurses Competence - Marcellina Putri S; Diah Arruum (Caring: Indonesian Journal of Nursing Science, 2026)
Infection Prevention and Control (IPC) is a core competency for nurses in hospital. However, several instances of infections caused by suboptimal nursing competencies in IPC are still observed, which can lead to patient safety issues. Nurse self-leadership is one way to enhance nursing competencies in IPC. This study aims to identify the relationship between self-leadership and nursing competencies in infection prevention and control in hospital. The research design used a descriptive correlation approach with a simple random sampling technique. The study was 98 nurses. This study was conducted using the Pearson correlation coefficient (r). The results of the study showed that nurse self-leadership was in the moderate category with a mean value of 3.06, and nursing competencies in infection prevention and control were also in the moderate category, with a mean value of 63.79. The study found a significant relationship between self-leadership and nursing competencies in infection prevention and control, with a r = 0.385, p-value 0.000 (< 0.05), indicating a weak relationship. The component of self-leadership that scored the highest was behavior-focused strategies. In conclusion, higher self-leadership among nurses is associated with better nursing competencies in IPC. It is recommended that ward managers develop the self-leadership skills and competencies of nurses in infection prevention and control through structured training programs. Improving self-leadership skills can enhance nursing competencies. Keyword: Hospital, Humans, Leadership, Patient Safety, Research Design